Inflammatory dendritic cells restrain CD11b+CD4+ CTLs via CD200R in human NSCLC - Mingjie Lin; Di Chen; Zheyu Shao; Qinyuan Liu; Zhixing Hao; Zhongwei Xin; Yongyuan Chen; Wenxuan Wu; Xiaoke Chen; Teng He; Dang Wu; Pin Wu (Cell Reports, 2024)
Summary: CD4+ cytotoxic T lymphocytes (CD4+ CTLs) are suggested to play a crucial role in inflammatory diseases, including cancer, but their characteristics in human non-small cell lung cancer (NSCLC) remain unknown. Here, using the cell surface marker CD11b, we identify CD11b+CD4+ CTLs as a cytotoxic subset of CD4+ T cells in multiple tissues of NSCLC patients. In addition, tumor-infiltrating CD11b+CD4+ CTLs show a dysfunctional phenotype with elevated expression of CD200 receptor (CD200R), a negatively immunomodulatory receptor. CD4+ regulatory T (Treg) cells restrain the anti-tumor role of CD11b+CD4+ CTLs via CD200. Mechanistically, inflammatory dendritic cells promote the CD200R expression of CD11b+CD4+ CTLs by secreting interleukin-1β (IL-1β). Finally, we demonstrate that CD200 blockade can revive the tumor-killing role of CD11b+CD4+ CTLs and prolong the survival of tumor-bearing mice. Taken together, our study identifies CD11b+CD4+ CTLs in NSCLC with decreased cytotoxicity that can be reinvigorated by CD200 blockade, suggesting that targeting CD200 is a promising immunotherapy strategy in NSCLC.